(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the lifestyle, living environment, and future wishes of older adults with chronic heart failure Methods: A cross-sectional descriptive study was conducted on older adults (≥ 60 years old) receiving outpatient treatment for chronic heart failure at Thong Nhat Hospital and University Medical Center Ho Chi Minh City from September to November 2025. Results: The survey included 130 older adults with chronic heart failure, with a median age of 70 [65–79]. Males accounted for 52.3%, and females for 47.7%. A total of 60.8% of patients preferred aggressive treatment at the end of life, while 39.2% opted for palliative care. Most patients (70.8%) expressed a wish to be cared for and die at home; however, 27.7% had not yet considered this issue. Female patients reported lower rates of alcohol and tobacco use compared to males. The most common comorbidities included hypertension (75.4%), dyslipidemia (66.9%), and chronic coronary syndrome (50.8%). Conclusions: Older patients with chronic heart failure require comprehensive management. This includes integrating advance care planning (ACP) into chronic heart failure management and considering gender differences in treatment counseling.